FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH KOTA SEMARANG TAHUN 2018-2022 - Romadon, Ahmad Sahri; Fridatien, Ericke (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This research aims to test the influence of the independent variables, namely hotel tax (X1), restaurant tax (X2), advertising tax (X3) and entertainment tax (X4) on the dependent variable, namely regional original income (Y) at the Semarang City Regional Revenue Agency 2018-2022.The sample used in this research was taken from tax realization reports selected using a purposive sampling technique. The analytical method used is the multiple linear regression analysis method which was tested using the SPSS 27 program application.The research results show that restaurant tax and entertainment tax have no effect on local original income, while hotel tax and advertising tax have a significant positive effect on local original income. Keywords: Hotel Tax, Restaurant Tax, Advertisement Tax, Entertainment Tax, and Regional Original Income.